Design and potentiostat circuit for neurochemical sensing / Ahmad Farhan Yahaya - Yahaya, Ahmad Farhan (2009)
This thesis presents electrochemical cell that will be applied to potentiostat circuit to show its characteristics. The potentiostat is used to measure the neurochemical that act as a neurotransmitter in human body like dopamine. The potentiostat circuit consists of electronic devices and components, including operational amplifier, to set up a control circuit for neurochemical sensing. The circuit is required to go under simulation tools such as PSice, Multisim or Simulink to design and simulate the circuit for analyzing its performance and parameters involved. The potentiostat circuit will amplify the signal current from the working electrode. The voltage source, Vsrc, of the circuit should be same with the voltage cell, Vcell, between reference electrode and working electrode. Output voltage is depending on current flow across electrochemical cell.